Associations between joint pathologies and central sensitization in persons with hand osteoarthritis: results from the Nor-Hand study. (24th September 2021) - Steen Pettersen, Pernille; Neogi, Tuhina; Magnusson, Karin; Mathiessen, Alexander; Hammer, Hilde Berner; Uhlig, Till; Kvien, Tore K; Haugen, Ida K
Abstract: Objective: Pain sensitization is associated with pain severity in persons with hand OA. What contributes to pain sensitization is unclear. This study explores whether hand OA pathologies and symptom duration are related to central sensitization. Method: Participants with hand OA in the Nor-Hand study underwent bilateral hand radiography and US examination. Central sensitization was assessed with pressure pain thresholds (PPT) at remote sites (wrist, trapezius and tibialis anterior muscles) and temporal summation. We examined whether hand OA pathologies, independent of each other, including structural severity (Kellgren–Lawrence sum score, presence of erosive hand OA), inflammatory severity (greyscale synovitis and power Doppler activity sum scores) and symptom duration, were related to central sensitization, adjusting for age, sex, BMI, comorbidities and OA-severity of knee/hip. Results: In 291 participants (88% women, median age 61 years, interquartile range 57–66 years) Kellgren–Lawrence, greyscale synovitis and power Doppler activity sum scores were not associated with lower PPTs at remote sites. Persons with erosive hand OA had lower PPTs at the wrist (adjusted beta −0.75, 95% CI −1.32, −0.19) and tibialis anterior (adjusted beta −0.82, 95% CI −1.54, −0.09) and had greater temporal summation (adjusted beta 0.56, 95% CI 0.12, 1.01) compared with persons with non-erosive disease. No associations were found for symptom duration. Conclusions: A person's overall amount of structural or inflammatory hand OA pathologies was not associated with central sensitization. Although persons with erosive hand OA showed greater signs of central sensitization, the small differences suggest that central sensitization is mainly explained by factors other than joint pathologies.